A human-centered development of local wisdom–based puzzle learning media for early childhood cognitive development - Kumara Dibya; Cahyani Kiftiasah (CV. SPDFHarmony, 2025)
Background: Early childhood is a critical period for cognitive development, during which children rapidly develop thinking, problem-solving, and symbolic abilities. Learning media play an important role in facilitating cognitive stimulation through play-based and concrete learning experiences. However, many educational puzzle media used in early childhood classrooms lack durability, cultural relevance, and human-centered design considerations. Integrating local wisdom into learning media offers opportunities to contextualize learning while strengthening children’s cultural identity. Aims: This study aims to develop and validate a local wisdom–based puzzle learning media designed to support cognitive development in early childhood, with a focus on media feasibility, teacher usability, and children’s engagement as key human factor indicators. Method: This study employed a Research and Development approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The learning media were developed in the form of an acrylic-based puzzle integrating Lampung local wisdom. Data were collected through expert validation sheets, teacher response questionnaires, and observations of children aged 5–6 years during small-scale and large-scale trials. Data were analyzed using descriptive quantitative analysis with a percentage-based approach. Results: The findings show that the developed puzzle media achieved very high validity scores from both media and subject-matter experts. Teacher responses indicated that the media were very attractive, easy to use, and appropriate for early childhood learning. Children demonstrated high levels of engagement, concentration, and cognitive interaction during both trial stages. Conclusion: Local wisdom–based puzzle learning media developed through a human-centered approach are feasible and attractive for early childhood cognitive learning. The integration of cultural content, durable materials, and user-oriented design enhances learning relevance and engagement.